Greeks in the Russian Empire and their Role in the Development of Trade and Shipping in the Black and Azov Seas (nineteenth – early twentieth centuries) - Shliakhov, Oleksei (The Historical Review/La Revue Historique, 2013)
The article aims to survey the role of Greek entrepreneurs in the development of trade and shipping in the Black and Azov Sea area. Based on hitherto under-analyzed Ukrainian archival records of Greek communities (in Odessa, Izmail, Nikolaiev, Kherson, Feodosiia, Berdiansk, Mariupol, Taganrog, Rostov-upon-Don and Kerch), the article explores the professional activities of Greek merchants, captains, engineers, pilots and sailors during the nineteenth century and the early twentieth.